Online Gaming Among Selected Junior High School Students (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
IntroductionThe COVID-19 pandemic, an ongoing global crisis, led to the unprecedented closure of schools, necessitating a rapid shift to distance learning modalities such as online classes and self-learning modules.  While confined to their homes, students found themselves with increased time and access to the internet and personal devices, enabling them to engage in various activities, including online gaming.  This surge in online gaming, facilitated by mobile phones and computers, became a notable trend during the pandemic. Numerous studies have examined the consequences of excessive online gaming, delving into its impact on physical health, psychosocial well-being, emotional states, and behavioral patterns.  Concurrently, a counter-narrative supported by research posits the potential benefits of online gaming, such as heightened student motivation, enhanced critical thinking, creativity, communication skills, and improved technological literacy.  However, the nuanced effects of online gaming on students' lives, especially during a period of confinement, remain a relatively unexplored domain. This study aimed to ascertain the extent to which online gaming affected respondents during the pandemic.  MethodThe researchers adopted a descriptive-correlational approach and collected data from 150 students spanning Grades 7 to 9 at Union Christian College.  A comprehensive questionnaire was used to gather pertinent information.  The data underwent quantitative analysis, employing frequency counts and percentages to depict respondent profiles and the extent of exposure to online games.  The weighted mean was calculated to assess the impact of online gaming across physical, psychosocial, emotional, and behavioral dimensions.  The Pearson Product Moment Correlation Coefficient was also employed to reveal potential relationships between variables. Results and Discussion Demographically, most respondents were female and enrolled in the 8th Grade.  Grade Point Average (GPA) distributions indicated that most students maintained satisfactory academic performance, with grades ranging from 80 to 94.  Among the most popular online game genres were shooting, action, and sports.  Notably, most respondents reported spending 1 to 5 hours online gaming, indicating a balanced approach to this activity. The analysis unveiled that, on the whole, online gaming exhibited a minimal impact on respondents, except for the emotional aspect, which moderately affected them.  Interestingly, the psychosocial aspect emerged as the least affected dimension.  Correlation analysis demonstrated a significant positive relationship between grade level and extent of exposure to online games, suggesting that higher-grade students were more immersed in online gaming.  Furthermore, GPA exhibited a negligible negative relationship with gaming exposure, implying that gaming duration largely unaffected academic performance. Correlations between respondent profiles and perceived effects indicated noteworthy patterns.  Grade level exhibited a significant positive correlation with perceived physical effects, implying that higher-grade students reported more pronounced physical impacts.  Conversely, GPA exhibited a significant negative correlation with perceived psychosocial effects, suggesting that students with higher academic performance attributed fewer psychosocial repercussions to gaming. Additionally, the types of online games played, and grade levels correlated positively with effects on the emotional aspect, underscoring the intricate relationship between gaming preferences and emotional responses.  Intriguingly, the extent of exposure to online games displayed a significant positive correlation with perceived psychosocial impacts, highlighting that greater exposure led to more substantial psychosocial effects. ConclusionOnline gaming platforms facilitated virtual communities where players could interact and socialize through text or voice chats.  The study's results collectively indicated that the surveyed students engaged in online gaming with moderation and that its effects on various aspects of their lives remained minimal.  However, the study recommended a balanced approach, advocating for guidance from parents and teachers in navigating the balance between academic pursuits and gaming engagement.  Parents, supported by teachers and schools, were encouraged to oversee this equilibrium, allowing students to enjoy gaming while ensuring their academic responsibilities were met.
Keywords: online gaming; online learning; junior high school